Planning Litigation in Ski Resorts as a Reflection of Territorial Conflicts in the French Northern Alps - Oriane Sulpice (Revue de Géographie Alpine)
Litigation over urban planning documents in mountain areas is a legal reflection of territorial conflicts that generate confrontations before administrative courts. The aim of this article is to show how legal rulings by the administrative courts have affected the drafting of local urban plans in twelve municipalities supporting major ski resorts in the Northern Alps of France between 2000 and 2017. It also looks at the recent ruling in May 2023 to overturn the territorial coherence plan for the Maurienne region. For these resorts, the intensification of real estate production determines their ranking in the competition between recreational destinations. Against this backdrop, legal challenges are bringing into question the extent to which those involved in mountain development are taking responsibility for environmental constraints. They represent a legal risk for urban planning documents, which ski resorts are not passive about and are developing strategies to resist.